HUBUNGAN MOTIVASI DENGAN TINDAKAN PAP SMEAR PADA WANITA USIA SUBUR DI WILAYAH KERJA PUSKESMAS - Komang Sri Widiani (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Cervical cancer is stated as the second cause of death of woman worldwide. An increased risk of cervical cancer every year is a serious threat for woman which highly related to their reproduction health. Short of awareness and less motivation to follow